THE INFLUENCE OF HEAVY METALS ON THE ABSORPTION OF CATIONIC DYES - Mustapa Mustapa; Aisyiah Restutiningsih Putri Utami; Chaleb Paul Maanari; Miftahul Jannah; Stefan Marco Rumengan (JURNAL PENA SAINS, 2024)
Cationic dyes are dyes containing amine derivatives that can be used on cellulose, protein, nylon, acrylic and synthetic fibers but these dyes are less fast in coloring. This study investigates the impact of Pb2+ heavy metal ions on cationic dye absorption utilizing molecularly imprinted polymers as adsorbents. Concentrations of Pb2+ ranging from 0 to 50 mg/L were examined. In a one-hour interaction, 50 mg of adsorbent was introduced into a solution containing 100 ppm methylene blue dye and Pb2+ with varying concentrations. Following centrifugation, the filtrate was collected, and dye concentration was measured using a visible light spectrophotometer. The sorption capacity of the dye with Pb2+ reached 41.22 mg/g at the highest concentration and 35.83 mg/g at the lowest. Notably, an inverse relationship was observed between Pb2+ concentration and absorption capacity, indicating a decrease as metal ion concentration increased, though stability was maintained. These findings contribute valuable insights into the nuanced dynamics of heavy metal ions and cationic dye absorption, shedding light on potential applications of molecularly imprinted polymers as effective adsorbents.